NAVIGATING GENUINE LEADERSHIP IN MILITARY ORGANIZATIONS UNDER VUCA CONDITIONS - CARAGEA MARIUS-EMANUEL (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The contemporary military environment is increasingly shaped by volatile, uncertain, complex, and ambiguous (VUCA) conditions, which present significant challenges to the adoption of genuine leadership. This article investigates how authentic leadership behaviors manifest in fast-paced, unpredictable operational settings-exactly the type of environment in which modern military forces often face difficulties in fulfilling their duties. Grounded in transparency, ethical conduct, and self-awareness, authentic leadership is crucial for building resilience and adaptability within military teams. This research examines how these leadership qualities can be applied to help military leaders effectively manage VUCA challenges, ensuring that personnel remain cohesive and capable of performing under pressure. By analyzing leadership practices in real-world contexts, this study seeks to offer insights into how authentic leadership can enhance military organizations’ ability to navigate uncertainty and achieve success in demanding circumstances.